FINANCIAL SECURITY OF DELEGATED AUTHORITIES OF LOCAL GOVERNMENT BODIES: PROBLEMS AND DIRECTIONS OF IMPROVEMENT - BENOVSKA, Liliya (Scientific journal «World of Finance», 2025)
Introduction. The financial provision of delegated powers of local authorities rests on two important problems: firstly, due to the lack of a clear and unambiguous legally enshrined division of powers of authorities and local self-government bodies, the source of their funding arises the problem of their duplication. Secondly, there is a discrepancy between the cost of delegated powers and the financial resources allocated for this purpose, which negatively affects the quality and availability of public services due to the inability of local authorities to exercise their powers. The purpose of the article is to study the problems and risks of financial support of delegated powers of local government bodies and search for ways to improve them. Results. It was revealed that the problems of legislative regulation of the distribution of powers of local authorities are based on the need to include mines in the constitution, which is a complex and long-term process. The analysis of the dynamics and structure of revenues and transfers from the state budget revealed the predominance of the share of targeted transfers in the structure of transfers and the simultaneous growth in the dynamics of the volumes of fixed revenues of local budgets. Conclusions. It is advisable to improve the financial provision of delegated powers of local authorities in several directions: conceptual separation of powers of local self-government bodies and executive power; improvement of methodological approaches to calculating the value of delegated powers; use of inter-municipal cooperation.